AN ANALYSIS OF LEXICAL COHESION IN SPEECH TEXT IN FOOD PRODUCT ADVERTISING VIDEOS - Rofiah Ulil Maftuha; Radinda Aqshalia Hidayah (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
Advertising as a discourse contains messages that want to be conveyed to society at large. Bango Ketchup, as one of the products that uses unique advertising, always tries to prioritize local culture as an element that must be present in their advertising. To reveal this message, it is necessary to dissect the discourse patterns used from the perspective of the socio-cultural situation, namely the lexical aspect. This research aims to reveal the meaning behind visuals by reading the signs presented in an advertisement. The process carried out, namely data analysis, is described using a qualitative descriptive approach. Research includes collecting various data from research subjects and relevant sources. Then the data is analyzed to gain an understanding of the study object at hand. Some of the activities in this research are collecting data by observation. Then sort and analyze the data. Then it ends by drawing conclusions from this research.